2017
DOI: 10.11606/0031-1049.2017.57.19
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the tigrina Leopardus tigrinus (Schreber, 1775) species group (Carnivora, Felidae)

Abstract: The tigrina Leopardus tigrinus (Schreber, 1775) is a small-sized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 49 publications
2
47
0
3
Order By: Relevance
“…The nine species are listed in Table 1 along with their mean body masses, sample sizes, study sites, and living-space sizes. The morphometric parameters of each species were within the values reported by Macdonald and Loveridge [30].…”
Section: Subjectssupporting
confidence: 75%
See 1 more Smart Citation
“…The nine species are listed in Table 1 along with their mean body masses, sample sizes, study sites, and living-space sizes. The morphometric parameters of each species were within the values reported by Macdonald and Loveridge [30].…”
Section: Subjectssupporting
confidence: 75%
“…The oncilla, traditionally considered to be a single species (Leopardus tigrinus), seems to encompass three distinct species, the one found in Argentina most likely being Leopardus guttulus [30]. It shares mountain forests and Andean moors with the puma and lowlands with the jaguar, puma, ocelot, jaguarundi, and margay [31].…”
Section: Introductionmentioning
confidence: 99%
“…Durante períodos de privação de nutrientes, um animal sadio vai perder glicogênio e gordura, e em contraste, pacientes doentes vão catabolizar massa corporal magra quando não forem providos suficientemente de calorias. Em animais debilitados, como o L. guttulus atendido, a resposta inflamatória é o gatilho que altera as concentrações de citocinas e hormônios e que rapidamente transforma o metabolismo para o estado catabólico [27]. Desta forma, o suporte nutricional para pacientes críticos é um importante componente do plano terapêutico.…”
Section: Discussionunclassified
“…The last specimen- 7 The oncilla (Leopardus tigrinus), if it really does occur in our region (see above), has unreversed nuchal fur (Nascimento and Feijó, 2017). based revision was Pocock's (1941), who assigned all the Peruvian material he examined to the subspecies L. p. aequatorialis (Mearns, 1902), the type locality of which is in the Pacific lowlands of northern Ecuador. Although Eizirik et al (1998) suggested that several phylogeographic partitions are present within L. pardalis, their study did not include any western Amazonian sequence data, so the assignment of our material to any of the phylogroups they recognized is problematic.…”
Section: Felidaementioning
confidence: 95%
“…The Matses description suggests the oncilla (Leopardus tigrinus), but other hunters consider the cachu bëdi to be a synonym for the margay. Although L. tigrinus was reported from Jenaro Herrera by Pavlinov (1994), we have not examined the voucher specimen (in Moscow), and in the absence of other records of this species from northeastern Peru (Nascimento and Feijó, 2017), we are reluctant to include it here.…”
Section: Felidaementioning
confidence: 99%